The Effect of application of some environmental recourse materials on the availability of some nutrients in the soil - G. AL-Fazani ,A. Abuzkhar , A.Tamazine , A. AL-Fahm , M. AL-fil (Journal of Pure & Applied Sciences, 2018)
This study was conducted to attempt to find the best combinations of seaweed ,solid sewage ,and municipal waste application rates to the soil as soil conditioner. Twenty six treatments with three replicates each where chosen from these environmental materials separately or combined to make an application rate of (20 t / ha ) added to (5 Kg) soil in plastic pots ,which were previously dried and sieved to pass (2 mm) sieve. The pots were put in a greenhouse chamber at ( 25 2 0C ) and 50% FC moisture content and kept for four months. At the end of this period ,samples were taken from each pot to be Analyzed for chemical and biological Analysis. Tomato seedlings (Tiem ) were planted in each pot and kept for another four months while care was taken to keep the temperature and moisture as mentioned earlier. During this period, the number of leaves and the plant heights where recorded periodically each month. At the end of this period ,the above soil portions of the plants were separated from the roots and washed with distilled water and put in perforated paper envelopes and dried at (650C) for two days. The dry weights of the two portions were recorded and the averages were calculated. The result obtained showed that the averages of the dry weight ranged between (7.65 – 19.73 g / pot) and an overall average of (11.94 g / pot) . The number of leaves ranged between (19 – 25) with an overall average of (21.65) while the plant heights ranged between ( 97 – 158 cm) with an overall average of (141 cm). Only seven treatment have given higher dry weights than the control (Soil alone). Generally, the dry weights decreased with increase in seaweed applications probably because of the high salinity.